Biodegradable-polymer versus durable-polymer drug eluting stents for coronary artery disease: systematic review and a meta-analysis. (25th November 2020) - Toyota, T; Morimoto, T; Kitai, T; Park, M; Sasaki, Y; Kim, K; Ehara, N; Kobori, A; Kinoshita, M; Kaji, S; Furukawa, Y; Kimura, T
Abstract: Background: Biodegradable polymer drug-eluting stents (BP-DES) has been developed to overcome the potential drawbacks of the first-generation durable polymer drug-eluting stents (DP-DES). However, it is still under debate whether BP-DES is associated with superior efficacy and safety over DP-DES. Purpose: We sought to compare the effects of BP-DES and DP-DES in patients with coronary artery disease. Methods: We performed systematic review and a meta-analysis of randomized controlled trials comparing BP-DES and DP-DES on clinical outcomes in patients with coronary artery disease using CE-mark approved drug-eluting stents (DES) with at least 1-year follow-up. We included 32 studies involving 39, 686 patients (BP-DES: 21, 439 patients, and DP-DES: 18, 247 patients). Primary outcome measure was target vessel failure (TVF; equivalent to the composite of cardiac death, target-vessel myocardial infarction, or ischemia-driven target vessel revascularization). We performed subgroup analysis according to the DP-DES generations (newer-generation DP-DES: 15, 179patients, and first-generation DP-DES: 3, 068 patients), and the effects of newer-generation DP-DES was compared with the BP-DES according to the BP-DES strut thickness (Ultra-thin strut [<80μm]: 7, 572 patients, Thin-strut [80–100μm]: 5, 465 patients, and Thick-strut [≥80μm]: 5, 876 patients). Results: The odds for TVF was not significantly different between the BP-DES group and the DP-DES group in the entire study population (odds ratio [OR] 0.96, 95% confidence interval [CI] [0.90–1.02], P=0.20). The odds for TVF was significantly low in the BP-DES group relative to the first-generation DP-DES group, however the odds were comparable between the BP-DES group and the newer-generation DP-DES group (BP-DES versus first-generation DP-DES: OR 0.82, 95% CI [0.73–0.92], P<0.001, and BP-DES versus newer-generation DP-DES: OR 1.00, 95% CI [0.93–1.08], P=0.99). We also found no significant differences between the BP-DES and newer-generation DP-DES, in all subgroups stratified by the BP-DES strut thickness (Ultra-thin strut BP-DES versus newer-generation DP-DES: OR 0.88, 95% CI [0.76–1.02], P=0.10, Thin-strut BP-DES versus newer-generation DP-DES: OR 1.01, 95% CI [0.90–1.13], P=0.89, and Thick strut BP-DES versus newer-generation DP-DES: OR 1.11, 95% CI [0.99–1.25], P=0.08). Conclusions: In this meta-analysis of randomized controlled trials evaluating clinical outcomes, there was no significant differences between BP-DES and DP-DES. We found beneficial effects of BP-DES relative to the first-generation DP-DES, however, there was no statistical differences between BP-DES and newer-generation DP-DES, irrespective of the BP-DES strut thickness. Funding Acknowledgement: Type of funding source: None